1987
DOI: 10.1007/bf00314082
|View full text |Cite
|
Sign up to set email alerts
|

Myoadenylate deaminase deficiency: absence of correlation with exercise intolerance in 452 muscle biopsies

Abstract: A histochemical assay was routinely performed of myoadenylate deaminase (MAD) in muscle biopsy specimens. MAD was absent in 13 cases, i.e. 2.9% of the specimens. In 10 cases the deficiency was confirmed biochemically. The diagnoses in the 13 patients were: polyneuropathy (n = 5), infantile spinal muscular atrophy (n = 3), congenital myopathy with type 2 fibre atrophy, facioscapulohumeral myopathy, polymyositis, myotonic dystrophy and hyperornithinaemia with gyrate atrophy of the retina. In contrast, 35 unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 23 publications
0
11
1
2
Order By: Relevance
“…19, 43, and 44 for reviews), and has been thought to cause AMP and ADP accumulation at high-energy demands, if the deficiency were great (49). The presence of AMPD deficiency is often associated with symptoms of exertional myalgia, such as muscle cramps and stiffness, as well as exaggerated fatigue and delayed muscle relaxation (11,49); however, deficits in muscle function are not necessarily independent of other myopathies (37). In fact, a large percentage of individuals with AMPD deficiency are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19, 43, and 44 for reviews), and has been thought to cause AMP and ADP accumulation at high-energy demands, if the deficiency were great (49). The presence of AMPD deficiency is often associated with symptoms of exertional myalgia, such as muscle cramps and stiffness, as well as exaggerated fatigue and delayed muscle relaxation (11,49); however, deficits in muscle function are not necessarily independent of other myopathies (37). In fact, a large percentage of individuals with AMPD deficiency are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…4, E and F). This was apparent when the peak rate of force development is compared between the groups over the contractions where the largest functional differences were apparent between the groups (contractions [35][36][37][38][39][40]. In fact, an inverse relationship with increasing contraction frequency was apparent in the AK1 Ϫ/Ϫ group and not in the WT muscle (Fig.…”
Section: Contractile Function the Initial Peak Tetanic Tension Was Nmentioning
confidence: 99%
“…Absence of MAD occurs in approximately 2% of muscle biopsy submitted to pathologic examination for suspected neuromuscular disease 6 . MAD deficiency have been described in muscle biopsy of patients with polyneuropathy, infantile spinal muscular atrophy, congenita myopathy with type-2 fiber atrophy, facioscapulohumeral myopathy, polymyositis, dermatomyositis, myotonic dystrophy, limb-girdle muscular dystrophy, dystrophinopathies, systemic sclerosis, McArdle's disease, phosphofructokinase deficiency, and hyperornithinaemia with gyrate atrophy of the retina 3,[7][8][9] . MAD deficiency associated with other neuromuscular disorders was previously thought to be the result of a limitation in MAD transcript availability, secondary to the pathological abnormalities in a variety of neuromuscular or rheumatological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports suggested that patients with MAD deficiency had a syndrome of myalgia, and exercise intolerance 2 . However, deficiency of the MAD has been described in many conditions, including myopathies, neuropathies, and motor neuron disease 3 . We report a patient with clinical diagnosis of myotonia congenita and absent myoadenylate deaminase reaction on the muscle biopsy.…”
mentioning
confidence: 99%
“…Screening studies with large numbers of muscle biopsies in Europe and America revealed a high prevalence of MAD of about 2-3% in all samples [33][34][35][36][37][38][39][40].…”
Section: Mad Deficiencymentioning
confidence: 99%